Pengembangan Media Pembelajaran Smart Box di Kelas VII UPTD SMP Negeri 1 Kota Gunungsitoli - Seofeto, Ayu Irani Oktavianti; Ndruru, Mastawati; Bawamenewi, Arozatulo; Waruru, Lestari (Indo-MathEdu Intellectuals Journal, 2026)
This study aims to develop Smart Box learning media for the Indonesian language subject, specifically on official letter material for Grade VII at UPTD SMP Negeri 1 Gunungsitoli. The method used in this study is research and development (R&D). The learning media developed uses the 4D model, which consists of four main stages: define, design, develop, and disseminate. The results of the study show that the learning media developed has undergone a validation process by three experts, namely a material expert, a language expert, and a design expert. The validation results indicate that the material expert gave a score of 75% in the "feasible" category, the language expert gave a score of 64% in the "feasible" category, and the design expert gave a score of 86% in the "very feasible" category. These percentages indicate that the Smart Box learning media that devel. The validation results show that the subject matter expert gave a score of 75% with the category 'feasible,' the language expert gave a score of 64% with the category 'feasible,' and the design expert gave a score of 86% with the category 'very feasible.' These percentages indicate that the Smart Box learning media developed meets the feasibility criteria from the aspects of content, language, and design appearance. The practicality of the Smart Box media received positive responses from the students. The trial results in the group showed a percentage of 91% with the category 'very practical.' This indicates that the media is practical to use in learning activities at school. The effectiveness of the Smart Box media is demonstrated through the learning completeness results of the students, which reached 91% in the field trial.